Bedouin Children and Their Reality Perceptions of the War Between Israel and Gaza. Issue 4 (1st October 2016) - Ben-Asher, Smadar
Abstract: In the military conflict between Israel and Gaza, the Bedouins in Israel find themselves under attack by rockets launched from Gaza, and at the same time identifying with family members in Gaza who suffer casualties as a result of Israel's operations. Bedouin children experience a threat to their safety, and are required to enter protected spaces when the siren sounds. Simultaneously, they are exposed to the Arab media, which one-sidedly views Israel as the aggressor. This study examines this complex situation from the perspective of Bedouin children aged 8–10, using children's drawings and letters, interviews, and conversations with their mothers. The findings reflect the children's complicated impression of the world, manifested in identification with the residents of Gaza and their suffering, anxiety concerning their own safety, and development of post-traumatic stress disorder. They have difficulty constructing a coherent picture of the world, and develop perceptions containing distortions of reality with regard to aggressor and victim. The findings indicate the need for professional intervention which, in addition to building a psychological assistance system, would provide parents with guidance to help them mediate the complex reality for their children in a structured and informed way, and hence enable them to better contend with it.‏